PENGEMBANGAN KORIDOR EKOWISATA BERBASIS POTENSI STRATEGIS DAERAH DI KABUPATEN ROTE NDAO - Apriana H.J. Fanggidae (Journal of Management Small and Medium Enterprises (SMEs), 2016)
Since the present trend is environmentally concerned and sustainable development policy, thus theconcept of tourism development by Local Government of Rote Ndao should concern about thattrend. Rote Ndao Regency has an abundance of biological and non-biological natural resources,however, in fact the people are remained living in below the poverty line, the agricultural sectordeclined, the lack of cooperation among the Government, community and stakeholder, the low levelof knowledge and information of stakeholders in managing and utilizing the potential of the regionas the leading tourism sector and the increasing degradation of natural resources which are notunder control. Considering the gap, researchers interested in conducting research on the developmentof area potential strategic-based ecotourism which was aimed : 1) to identify and to verify theproductivity of various commodities, horticulture agricultural integrated systems 2) streamliningLontar’s production system and the production of beef cattle/Buffalo and its effects on smallbusiness/community groups 3) efficiency of the ocean and the land areas in order to maintain andpreserve the uniqueness and richness of the available ecosystem 4) to improve the understanding oflocal society and stakeholders in order to have concern, responsibility and commitment to thepreservation of the environment and culture through workshop preparation about development ofecotourism corridor in Rote Ndao Regency. This research is applied research to solve practicalproblems that are classified into research development or action research using a descriptivequalitative analysis which consists of the analysis of the potential strategic areas profile, analysis ofefficiency, analysis of promotion and analysis of ecotourism. The development model of areapotential strategic-based ecotourism used the SWOT analysis (strength, weakness, opportunity andtreat). Data analysis known that : Rote Ndao Leading Sector comprises 5 sectors namely : 1)Agriculture 2) Plantation 3) Livestock 4) Fisheries and 5) TourismKeywords: development, ecotourism, potential, strategic, Rote Ndao